Hubungan Forgiveness dan Kualitas Pernikahan Pada Istri - Antika, Rindi; Khumas, Asniar; Jafar, Eka Sufartianinsih (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Forgiveness is the process of letting go of anger and resentment towards someone who has hurt you. Forgiveness is important in marital relationships because it can improve marital quality, such as marital satisfaction, communication, and intimacy. The purpose of this study was to determine the relationship between forgiveness and marital quality in wives. This study used a quantitative method involving 200 respondents using Simple Nonrandom sampling technique. The data obtained were analyzed using the Spearman’s Rho correlation technique, with the result that there was a relationship between forgiveness and marital quality in wives. The results of the study showed that there was a positive relationship between forgiveness and marital quality with a correlation of r = 0.929 and a significance value of 0.001 (p 0.05), meaning that the higher the forgiveness, the higher the marital quality. This indicates that forgiveness is an important factor that can improve marital quality. The implications of this research recommends that the government (KUA) provide education to prospective couples about the importance of forgiveness training in the household to improve the quality of marriage. .